Teaching Speaking Through the Use of Aleta Malebbie Application - Masruddin; Imran, Ali; Trihauli, Afnan Danin; Wulandari, Wulandari; Nur, Muh. Ilham (Institut Agama Islam Negeri Palopo, 2023)
This study aims to analyze the effectiveness of using Aleta Malebbie application in teaching speaking at IAIN Palopo. Using an experimental research method, this study involved 15 fifth semester students who were tested using a pre-test and post-test in the form of a speaking test. The data was analyzed using SPSS 22 with a t-test to determine the significance of the difference in the results before and after the treatment. The results showed that the Aleta Malebbie application was effective in improving students' speaking skills, as indicated by the increase in the average score of the post-test compared to the pre-test.